Remote control of AMPK via extracellular adenosine controls tissue growth - Zhang, Yao; Straßburger, Katrin; Teleman, Aurelio A. (Nature cell biology, 2025)
Adenosine monophosphate (AMP)-activated protein kinase (AMPK) is a regulator of cellular catabolism that is activated by AMP. As AMP accumulates in cells with low ATP, AMPK is considered a stress-activated kinase. While studying organ growth during Drosophila development, we find that AMPK can also be activated by a signalling metabolite not related to stress. Specifically, we find that two physiological inputs known to regulate organ growth rates (ecdysone (a steroid hormone) and dietary protein) modulate expression of adenosine deaminase in the intestine. This, in turn, alters circulating adenosine levels. Circulating adenosine acts as a signalling molecule by entering cells, becoming phosphorylated to AMP and activating AMPK to inhibit organ growth. Thus, AMPK activity is regulated developmentally, and AMPK activity in one tissue can be remote controlled by another tissue via circulating adenosine. Notably, this mechanism accounts for half the effect of dietary protein on tissue growth rates in Drosophila.